Land and the US Agrarian South. (April 2022) - Ajl, Max
This review essay summarizes and synthesizes three books on Black and Indigenous agrarian struggles in the modern-day territories of the USA. It discusses how they recount the centrality of land, national liberation, self-reliant development, food sovereignty and sustainable forms of agriculture and land management to Black and Indigenous radical struggle. It then suggests parallels and divergences between those struggles and those in the Third World's agrarian south. It focusses on the anti-systemic dimensions of national liberation struggles in the core, especially those carried out historically by Black and Indigenous movements, and details how those movements historically looked out beyond the US landmass for solidarity and to build internationalist fronts. Finally, it reflects on their role in destabilizing settler-capitalism in the USA.